(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, based on the comparative-typological structural method, that is, a comparative analysis of epic plots, characters and normative structures, a comparative analysis of some initial events in the plot of the epics "Alpomish" and "Manas" is carried out. The similarities and differences between the two epics and the specifics of the two folk oral works are studied.